Revision Surgery in Permanent Patellar Dislocation in DiGeorge Syndrome. (13th December 2015) - Berruto, Massimo; Parente, Andrea; Ferrua, Paolo; Pasqualotto, Stefano; Uboldi, Francesco; Usellini, Eva
Abstract : A 29-year-old patient, suffering from DiGeorge syndrome, came to our attention with a history of persistent pain and patellar instability in the left knee after failure of arthroscopic lateral release and Elmslie-Trillat procedure. The patient was unable to walk without crutches and severely limited in daily living activities. Because of arthritic changes of the patellofemoral joint and the failure of previous surgeries it was decided to perform only an open lateral release and medial patellofemoral ligament (MPFL) reconstruction using a biosynthetic ligament in order to obtain patellofemoral stability. At one year post-op range of motion (ROM) was 0–120 with a firm end point at medial patellar mobilization; patella was stable throughout the entire ROM. All the scores improved and she could be able to perform daily activity without sensation of instability. Bilateral patellar subluxation and systemic hyperlaxity are characteristics of syndromic patients and according to literature can be also present in DiGeorge syndrome. MPFL reconstruction with lateral release was demonstrated to be the correct solution in the treatment of patellar instability in this complex case. The choice of an artificial ligament to reconstruct the MPFL was useful in this specific patient with important tissue laxity due to her congenital syndrome.